Student evaluations of professors: Does a professors’ gender, race, or age influence student ratings? - Adibifar, Karam (International Journal of Active Learning, 2019)
Abstract The purpose of this study is to examine and describe whether students’ ratings of professors are influenced by the professor’s gender, age, and race. A survey is used to collect data. The sample (n= 319) used in this study is drawn from 16 different undergraduate classes taught by 9 different instructors. Students in this survey are enrolled in required general studies courses from a large-size public university in Southwestern United States. Using analysis of variance and frequency distribution, the findings reveal that professors’ gender, race, and age are related to how they are rated by students. The findings also indicate that female and male students differ in rating their professors. Furthermore, the research findings suggest that professors’ attitudes and interactions, as well as whether or not they post student grade, or accept students’ assignments online affects student ratings of professors.